EXAMINING THE VALUE OF LEADERSHIP IN NURSE PRECEPTORS FOR THE CLINICAL EXPERIENCES OF UNDERGRADUATE NURSING STUDENTS - Noura Hamoud Alqahtani, Nourh Yosef Abdullah Alabdulaziz, Amirah Sayah Sabih Alkuwaykibi, Abdulhadi Jafar Ali Alqahtani, Aeidha Aowed Jaber Alsulami, Haya Fahd Hamad Al Dosari; Manal Khalaf Al Duyayk, Mosaad Sayer Alruwaily, Munayfah Eid Alruwaili, Turki Salem Mohmmed Al Bahri, Sarah Mutair Albanaqi, Sahar Ali Harbosh (Chelonian Research Foundation, 2022)
The significance of leadership in nurse preceptors on the practical experiences of undergraduate nursing students is examined in this study. Currently, students are supervised by registered nurses (RNs), but many RNs are neither prepared or willing to take on this responsibility. For novice nurses, inconsistent supervision exacerbates the theory-practice divide and fosters a toxic learning environment. The study looks into how students think a nurse preceptor should be able to lead. Results show that students respect preceptors who are encouraging, helpful, and have effective communication skills. Effective clinical leadership is synonymous with these attributes. Keywords: theory-practice gap, clinical experience, nursing education, leadership development, and nurse preceptorship